Representations of Mary Magdalene in the Narrative of Jesus Christ's Marriage: A Study of Religious and Historical Manuscripts - Alda Malik; Arifinsyah Arifinsyah (Al-Adyan: Journal of Religious Studies, 2026)
This study examines the representation of Mary Magdalene in the narrative of her relationship with Jesus Christ through a historical-critical approach to the canonical texts, apocryphal texts, and modern literature discussing the subject. The study is motivated by the longstanding debate in the historiography of early Christianity regarding Mary Magdalene's position, whether as a prominent disciple, the witness to the resurrection, or a figure who has been variously portrayed in theological traditions and popular culture. This research employs a library research method using a historical-critical approach and comparative textual analysis. The findings indicate that the canonical texts primarily portray Mary Magdalene as a witness to the resurrection and a devoted follower of Jesus, whereas the apocryphal texts and modern discourse offer more diverse interpretations of her relationship with Jesus. However, differences in textual authority, historical context, and the temporal distance between these sources demonstrate that the claim of a marriage between Jesus and Mary Magdalene cannot be established as historical fact. This study underscores the importance of distinguishing between historical evidence, theological interpretation, and cultural construction when interpreting the narrative of Mary Magdalene. Penelitian ini mengkaji representasi Maria Magdalena dalam narasi relasinya dengan Yesus Kristus melalui pendekatan historis-kritis terhadap teks kanonik, teks apokrif, dan literatur modern yang membahasnya. Kajian ini berangkat dari perdebatan panjang dalam historiografi Kekristenan awal mengenai posisi Maria Magdalena, baik sebagai murid penting, saksi kebangkitan, maupun figur yang kemudian dipersepsikan secara beragam dalam tradisi teologis dan budaya populer. Metode penelitian yang digunakan ialah penelitian kepustakaan dengan pendekatan historis-kritis dan analisis tekstual-komparatif. Hasil kajian menunjukkan bahwa teks kanonik menempatkan Maria Magdalena terutama sebagai saksi kebangkitan dan pengikut Yesus, sedangkan teks apokrif dan wacana modern menghadirkan interpretasi yang lebih beragam tentang kedekatan relasionalnya dengan Yesus. Namun, perbedaan tingkat otoritas, konteks penulisan, dan jarak historis antarteks menunjukkan bahwa klaim mengenai pernikahan Yesus dan Maria Magdalena tidak dapat dipastikan sebagai fakta sejarah. Penelitian ini menegaskan pentingnya membedakan antara data historis, interpretasi teologis, dan konstruksi budaya dalam membaca narasi Maria Magdalena.